Genome editing without the hassles of tissue culture: Hope for editing plants recalcitrant to in vitro manipulations: GENOME EDITING : HOPE FOR EDITING PLANTS RECALCITRANT TO IN VITRO MANIPULATIONS - PAPA RAO VAIKUNTAPU; V DINESH KUMAR; M SUJATHA; T RADHAKRISHNAN (Journal of Oilseeds Research, 2020)
Genome editing has become a breakthrough technology this decade to preciselymodify the genome in short time. This technology has paved way for manipulating the traits of agronomic importance with ease in many crop plants. Even though plant transformation is necessary in the first step, the final product is non-transgenic; thus, attractive for social acceptance. Lack of robust transformation procedures is a limitation to use the genome editing in some crop plants. It becomes even harder when the frequency of precise editing effected by the reagents is low. Recent reports show that genome editing can be performed bypassing the tissue culture procedures; therefore, offer hope for its use in crops that are unresponsive. We briefly discuss these breakthrough techniques here.